Factors Associated with Aspirin Resistance in Hong Kong Chinese Patients with Stable Coronary Heart Disease Using the Multiplate® Analyzer and Serum Thromboxane B2 - Weiwei Zeng; Tanya T. W. Chu; Elaine Y. K. Chow; Miao Hu; Benny S. P. Fok; Juliana C. N. Chan; Bryan P. Y. Yan; Brian Tomlinson (MDPI AG, 2022)
Introduction: Aspirin resistance may be associated with various conditions. We measured serum thromboxane B2 (TXB2) and platelet function using the Multiplate® Analyzer with arachidonic acid (ASPI) in patients on long term aspirin therapy to identify aspirin resistance and associated factors. Materials and Methods: Chinese patients with stable coronary heart disease had samples for serum TXB2 and ASPI measurement taken before and 1 h after taking a morning dose of 80 mg aspirin. Results: In 266 patients with mean age 66.6 ± 10.7 years, 17% were female and 55% were current or previous smokers. TXB2 and ASPI measurements were significantly higher before the dose than at 1 h post dose, with 46% of subjects having high ASPI values (AUC > 300 AU*min) pre dose compared with 27% at 1 h post dose. TXB2 and ASPI measures of platelet aggregation showed weak correlations, which were only significant before the dose (r = 0.219, p = 0.001). Increased ASPI measurements were associated with white blood cell (WBC) count, haematocrit, platelet count and heart rate at 24 h post dose but only with WBC count, smoking history and heart rate at 1 h post dose. Diabetes was not associated with reduced platelet response to aspirin. The WBC count associated with aspirin resistance was over 6.55 × 109/L by receiver operating characteristic analysis. Conclusions: The antiplatelet response to aspirin was reduced in a large proportion of patients. Patients with higher WBC count within the normal range appear to be at increased risk of aspirin resistance. Higher or more frequent doses of aspirin may be needed in many patients.